GAMBARAN KEBAHAGlAAN PADA WARIA - Togiaratua Nainggolan (Sosio Konsepsia, 2010)
This study aims to describe the picture of happines on male to female transvestites, therefore conducted the research with a qualitative approach. The research location is place where male to female transvestites are often peddle themselves in intersection road Cileungsi Bogor-West Java. The main informant on weight of each life satisfaction domain in life. Who's affective evaluation occurs when the male to female transvestites make judgements of life satisfaction based on their appreciation of the meaning of life importants to them. In this case emphasizes the subjective evaluation of positive emotions wich the cubject live in the past, present, and the future. The peak of happiness for male to female male to female transvestites research is determined Â by purposive sampling (typical) based on the problem and research puprposes. The ensure the credibiliiu of the research, carried out the source and method triangulation in the prosess of data collection. Further desciptive data analysis conducted in accpordance with the objectives of qualitative research. The result, alihoughi the social burden of psychological, male to female transvestites capable of achieving happiness in his own way. The picture of happiness male to female transvestites in each individual (subjec-tive well being), and occurs happens when male to female transvestites make judgements based transvestites to come from the abiliii] to identifij and use the power (strength) owned in the daily lives. In line with the above research findings, researcher recommend (1) considering the various limitations in the process of this study, the researcher expected to involve an informant that further more with more varied characteristics, (2) for the happiness and social welfare male to female transvestites as fellow human beings, to Directorate of Sevices Social and Social Rehabilitation Ministnj Social Affairs, and other relevantr agencies, as toellas praktisioners engaged in the handling of male to female transvestites in the central and local levels so that more intensive provides empotoemenii for male to female transvestites to facilitate the evaluation process og cognitive and affective evaluations in his life.